Does technology-based interventions in psychosis improved functioning and quality of life? A systematic review and meta-analysis - Morales-Pillado, C.; Sánchez-Gutiérrez, Teresa; Fernández-Castilla, Belén; Barbeito, Sara; González-Fraile, Eduardo; Calvo, Ana (European Psychiatry, 2023)
Introduction: Technology-based interventions (TBIs), including computer and Internet-based interventions, mobile interventions, health applications, social media interventions, and interventions using technological devices, could become a useful, effective, accessible, and cost-effective approach (Berry et al., 2016; Firth, 2016) to complement conventional interventions for psychosis
Keywords: psychosis; quality of life; JCR